KEMAMPUAN MENGHASILKAN KEUNTUNGAN USAHA MIKRO KECIL MENENGAH DI KOTA DENPASAR DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Gde Bagus Brahma Putra; Ida Ayu Nyoman Yuliastuti (Juara: Jurnal Riset Akuntansi, 2019)
The purpose of this study is to test and obtain empirical evidence of the influence of entrepreneurialspirit, education level, business capital, marketing costs and length of businessto the ability of SMEs in generating profits in the city of Denpasar. The research was conductedon Small and Medium Micro Enterprises in Denpasar City. Sampling method using proportionalrandom sampling. Data analysis technique using multiple linear regression analysis. Theresults showed that the entrepreneurial spirit, business capital, marketing costs and businessduration positively influence the ability of SMEs in generating profits, while the variable level ofeducation has no effect.